Pengaruh Flash Sale Program, Persuasive Communication dan Produk Quality terhadap Purchase Decision - Ananda Yuliasa Azhari; Dedy Ansari Harahap; Septiana Ayu Estri Mahani (UNISBA Press, 2023)
Abstract. One of the achievements of a company's success is to make purchasing decisions for consumers, because it will provide benefits to the company in the long term. This is also what Unico wants to achieve, which has experienced a decline and increase in sales in several months due to the implementation of flash sale programs, persuasive communication and product quality, which affect the number of consumers who make purchases. This study aims to find out how the description, as well as the influence of flash sale programs, persuasive communication and product quality on purchase decisions at Unico. This research is a type of descriptive and verification research with quantitative methods. The sampling technique used is nonprobability sampling, namely purposive sampling. The population in this study were consumers who had purchased Unico products and obtained a sample of 255 people. Data analysis used is descriptive and verification analysis using multiple linear regression analysis, F test, t test, and coefficient of determination. The results of this study indicate that the flash sale program partially has a significant effect on the purchase decision, persuasive communication partially has a significant effect on the purchase decision and product quality has a significant effect on the purchase decision. Then simultaneously the flash sale program, persuasive communication and product quality have a significant effect on purchase decision. Abstrak. Tercapainya keberhasilan suatu perusahaan salah satunya adalah menciptakan keputusan pembelian pada konsumen, karena akan memberikan keuntungan kepada perusahaan dalam jangka waktu yang panjang. Hal tersebut juga ingin dicapai oleh Unico yang pernah mengalami penurunan dan peningkatan penjualan di beberapa bulan, akibat penerapan flash sale program,, persuasive communication dan product quality sehingga mempengaruhi jumlah konsumen yang melakukan pembelian. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran, serta pengaruh flash sale program,, persuasive communication dan product quality terhadap purchase deision di Unico. Penelitian ini merupakan jenis penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu purposive sampling. Populasi pada penelitian ini adalah konsumen yang sudah melakukan pembelian produk Unico dan didapatkan sampel yaitu sebanyak 255 orang. Selanjutnya, analisis data yang digunakan adalah analisis deksriptif dan verifikatif yang menggunakan analisis regresi linier berganda, uji F, uji t, dan koefisien determinasi. Hasil dari penelitian ini menunjukkan bahwa flash sale program, secara parsial berpengaruh signifikan terhadap purchase decision, persuasive communication secara parsial berpengaruh signifikan terhadap purchase decision dan product quality berpengaruh signifikan terhadap purchase decision. Lalu secara simultan flash sale program,, persuasive communication dan product quality berpengaruh signifikan terhadap purchase decision.